New sodium-based materials and their use as cathode materials or sodium-ion batteries
By using Na3-x□xV(2-y)My(PO4)2F(3-z)Oz/2 material for electrochemical modification, the problem of insufficient reversible sodium ions extraction of the positive electrode material of the existing Na ion battery is solved, and a higher reversible capacity and energy density is achieved, and the cycle life is extended.
Patent Information
- Application Number
- CN201980028260.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-04-26
- Filing Date
- 2019-04-25
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2039-04-25
AI Technical Summary
The positive electrode material of existing Na ion batteries, Na3V2 (PO4)2F3, can only reversibly extract two sodium ions, resulting in insufficient reversible capacity and energy density and short cycle life.
Na3-x□xV(2-y)My(PO4)2F(3-z)Oz/2 material is used, which reversibly absorbs and removes more than two sodium ions through electrochemical modification, and has a disordered quadrilateral space group I4/mmmm.
The reversible capacity and energy density of Na ion batteries are improved, and the cycle life is extended, so that the battery maintains a high capacity retention capability during continuous cycles.
Smart Images

Figure CN112106246B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of Na-ion batteries and provides a new Na-based material. The invention also relates to a method for preparing the material and its use as a positive electrode material.
[0002] The present invention also relates to a positive electrode material comprising the Na-based material, and to a Na-ion battery comprising the positive electrode. Background Art
[0003] In terms of chemical element abundance and cost, the most attractive option for lithium-ion batteries is sodium. Batteries using sodium ions as shuttle ions are used to replace lithium in applications where energy storage density is not as important as in portable electronics or automotive transportation, especially for the management of renewable energy sources. This realization has led to a revival of the sodium-ion battery concept and an intense activity dedicated to the exploration of high-performance electrode materials.
[0004] The performance of Na-ion batteries is related to the capacity of the cathode material, and the cathode material currently mainly uses Na3V2(PO4)2F3 material (NVPF). The material can insert and remove two sodium ions in each formula unit, resulting in a reversible capacity of 120 mAh / g.
[0005] Bianchini et al. (Chemistry of Materials, 2014, 26(14): 4238-47) disclosed the preparation of Na3V2(PO4)2F3 material and its use as a positive electrode material, and explained that only two sodium ions can be reversibly extracted in sodium ion batteries.
[0006] Gover et al. (Solid State Ionics 177 (2006), 1495-1500) disclosed that complete extraction of sodium from Na3V2(PO4)2F3 materials results in some irreversible structural degradation of the Li / / Na3V2(PO4)2F3 cell used for the extraction. Removal of the third sodium ion has never been developed because the process is considered irreversible.
[0007] Therefore, there is a need to provide a new Na-based material that can be used in Na-ion batteries that exhibit improved performance compared to prior art Na-ion batteries. Summary of the invention
[0008] The object of the present invention is to provide a Na-ion battery having an increased reversible capacity and an increased energy density compared to the Na-ion batteries described in the prior art.
[0009] Another object of the present invention is to provide a positive electrode material having a better cycle life than the prior art.
[0010] Materials of formula (I)
[0011] Therefore, the present invention relates to a material of formula (I):
[0012] Na 3-x □ x V (2-y) M y (PO4)2F (3-z) O z / 2 (I)
[0013] in:
[0014] 2 <x≤3;
[0015] 0≤y≤1;
[0016] 0≤z≤1;
[0017] □ represents a vacancy; and
[0018] M represents a transition or non-transition metal ion.
[0019] Preferably, in the material of formula (I) of the present invention, M is selected from the group consisting of magnesium, zinc, iron, aluminum, nickel, cobalt, chromium, titanium, manganese and mixtures thereof, preferably M is aluminum.
[0020] Typically, x, y, and z are selected to ensure electroneutrality of the compound.
[0021] Advantageously, in the material of formula (I), y=0 and / or z=0.
[0022] According to a preferred embodiment of the present invention, in formula (I), x is 2.25, 2.35, 2.5 or 2.75.
[0023] Preferably, the material of formula (I) can reversibly absorb and remove more than two sodium ions.
[0024] Advantageously, the material of formula (I) is disordered, meaning that the sodium ions are arranged in a disordered manner. Therefore, the material of formula (I) has a structure of a tetragonal space group I4 / mmm. The disorder is irreversible. The structure of the material of formula (I) can be found by XRD diffraction. The higher the x value, the higher the observed disordered phase formation.
[0025] Preparation method of material of formula (I)
[0026] The present invention also relates to a method for preparing the material of formula (I), comprising the following steps:
[0027] i) preparing a Na-ion battery comprising at least one positive electrode, at least one negative electrode and at least one electrolyte, wherein the positive electrode comprises a Na-based material (A) selected from the group consisting of:
[0028] οNa3V2(PO4)2F3;
[0029] οNa3V (2-y) M y (PO4)2F3;
[0030] οNa3V (2-y) M y (PO4)2F (3-z) O z / 2 ;and
[0031] ο mixtures thereof;
[0032] y, z and M are as previously defined in formula (I);
[0033] ii) making the Na ion battery obtained at the end of step i) at 4.3V to 4.8V (Na + / Na 0 ), preferably at a potential of 4.8 V, constant current and constant voltage charging, maintaining the battery at such a potential until more than two Na ions are extracted from material (A), wherein the amount of Na ions is determined by coulometric method; and
[0034] iii) obtaining a material of formula (I).
[0035] Advantageously, using this method, up to three sodium ions can be reversibly extracted from material (A) to obtain the material of formula (I).
[0036] Preferably, in step ii) of the process according to the invention, the amount of extracted sodium ions is measured by coulometry (in particular by controlled potential coulometry, i.e. the potential applied to the cell is constant). Coulometric methods make it possible to calculate the number of electrons passing through a material. In particular, the variation of the current with respect to time is monitored in order to calculate the total charge passing through the material. The technique can be implemented in constant current mode (i.e. the current value is fixed) or in constant potential mode (constant voltage mode). The charge is proportional to the amount of sodium ions extracted from material (A).
[0037] The potential applied in step ii) is 4.3 V to 4.8 V (Na + / Na 0 ). + / Na 0 ) indicates that the potential is relative to Na + / Na 0 The potential of (which is the reference potential) is defined.
[0038] In step ii) of the method, a galvanostat or a potentiostat such as .
[0039] In this method, the material of formula (I) is prepared in situ.
[0040] Advantageously, after step iii), the sodium ions (more than 2) extracted from material (A) to form the material of formula (I) can be reinserted into the newly formed material of formula (I) by releasing the potential applied to the Na-ion battery from 4.3 V to 4.8 V down to 1 V.
[0041] The material of formula (I) obtained at the end of step iii) of the method of the present invention can be used immediately or stored, preferably stored under an inert atmosphere.
[0042] positive electrode
[0043] Advantageously, the positive electrode implemented by the above method comprises material (A), a current collector, a polymer binder and an electronically conductive agent.
[0044] Preferably, the positive electrode further comprises a Na-based oxide material (B), such as Na x’ M’O2 (0 < x’ ≤ 1), where M’ represents at least one metal ion selected from the group consisting of: nickel, zinc, cobalt, manganese, iron, chromium, titanium, copper, vanadium, aluminum, magnesium and mixtures thereof. Generally, the material (B) is Na 2 / 3 Fe 1 / 2 Mn 1 / 2 O2.
[0045] The polymer binder as described above imparts mechanical strength to the electrode material and is preferably a polymer having a high elastic modulus (e.g., on the order of several hundred MPa) and stable under the temperature and voltage conditions at which the positive electrode is to operate. The binder provides high adhesion strength between the electrode material and the current collector, maintains electronic conductivity, and promotes electrolyte immersion into the electrode material, thereby forming a stable interface between the electrode and the electrolyte. The binder can be selected from polyvinylidene fluoride and poly(tetrafluoroethylene), cellulose fibers, cellulose derivatives such as starch, carboxymethyl cellulose (CMC), diacetyl cellulose, hydroxyethyl cellulose or hydroxypropyl cellulose, styrene-butadiene rubber (SBR) and mixtures thereof.
[0046] The amount of the binder can be 0 to 40% by weight, preferably 1 to 10% by weight, relative to the total weight of the materials of formula (A) and (B).
[0047] The electronically conductive agent can be selected from the group consisting of: carbon black, super carbon black, acetylene black, ketjen Channel black, natural or synthetic graphite, carbon fibers, carbon nanotubes, vapor grown carbon fibers or mixtures thereof.
[0048] According to the present invention, "carbon black" is a material in the form of semicrystalline carbon having a high specific surface area / volume ratio and produced mainly by the incomplete combustion of heavy petroleum products. Acetylene black and channel black are subtypes of carbon black.
[0049] According to the present invention, carbon fibers, carbon nanotubes and vapor-grown carbon fibers are cylindrical nanostructures of carbon comprising graphene layers arranged as stacked cones, cups or plates.
[0050] The amount of the electronically conductive agent may be 0 to 40% by weight, preferably 1 to 10% by weight, relative to the total weight of the materials of formula (A) and (B).
[0051] The current collector is a material with high electrical conductivity. Corrosion resistance, mechanical strength and flexibility enable it to withstand manufacturing operations (such as pasting and rolling), etc. According to the present invention, the current collector can be composed of an electronically conductive material, more specifically, a metal material selected from aluminum, copper, nickel, steel, titanium, tungsten, tantalum and carbon foil.
[0052] Advantageously, in the positive electrode, the amount of material (A) is 0.1% to 100% by weight, and the amount of material (B) is 0 to 99.9% by weight, relative to the total amount (weight) of the electrode material. Preferably, the amount of material (A) is 45 to 100% by weight, and the amount of material (B) is 0 to 55% by weight, relative to the total amount (weight) of the electrode material.
[0053] The positive electrode as defined above and implemented in the method of the present invention can be prepared according to the following steps:
[0054] a) mixing material (A) with a binder and an electronic conductive agent to obtain a mixture;
[0055] b) dispersing the mixture obtained in step a) in a solvent to form a slurry;
[0056] c) casting the slurry obtained at the end of step b) on a current collector to obtain a positive electrode;
[0057] d) drying the positive electrode obtained at the end of step c) at a temperature of 60° C. to 300° C., preferably at 120° C.;
[0058] e) pressing the dried positive electrode obtained at the end of step d) using a roller press.
[0059] The mixing step a) can be carried out by mixing in a mortar with a pestle or by a ball milling process.
[0060] In step b), the mixture obtained in step a) is preferably dispersed in a solvent selected from the group consisting of N-methyl-2-pyrrolidone (NMP), acetonitrile, ethanol, water and mixtures thereof. Typically, step c) is performed using an electrode coater.
[0061] Advantageously, a calender (such as CLP 2025H) performs step e).
[0062] negative electrode
[0063] The negative electrode of the present invention may include material (C). Similar to the positive electrode, the negative electrode may further include a current collector, a polymer binder and an electronic conductive agent as defined above.
[0064] This negative electrode can be prepared according to the following steps:
[0065] a') mixing material (C) with a binder and an electronic conductive agent to obtain a mixture;
[0066] b') dispersing the mixture obtained in step a') in a solvent to form a slurry;
[0067] c') casting the slurry obtained at the end of step b') onto a current collector to obtain a negative electrode;
[0068] d') drying the negative electrode obtained at the end of step c') at a temperature of 60° C. to 300° C., preferably at 120° C.;
[0069] e') pressing the dried negative electrode obtained at the end of step d') using a roller press.
[0070] The mixing step a') can be carried out by mixing in a mortar with a pestle or by a ball milling process.
[0071] Steps b')-e') are similar to steps b)-e) defined previously.
[0072] The material (C) of the negative electrode may be selected from the group consisting of hard carbon, antimony, tin, sodium, phosphorus, and mixtures thereof.
[0073] According to the present invention, "hard carbon" is a carbonaceous compound that obeys the "calorie reduction model" in which graphene layers (2 or 3 layers) are randomly stacked to form nanoscale pores. The material is described in Stevens et al. (Journal of the Electrochemical Society, 147 (4) 1271-1273 (2000)) and in Dhan et al. (Carbon Vol. 35, n°6, pp. 825-830). The binder and electronic conductive agent contained in the negative electrode are similar to those contained in the positive electrode and are as described above.
[0074] Preferably, the amount of material (C) varies from 80% to XX 99% relative to the total amount of negative electrode material.
[0075] The current collector of the negative electrode preferably contains aluminum.
[0076] Electrolyte
[0077] The electrolyte implemented in the method of the present invention is generally a solution comprising a solvent and a salt (preferably a sodium salt). The solvent can be a liquid solvent, optionally a liquid solvent gelled by a polymer; or a polar polymer solvent, optionally a polar polymer solvent plasticized by a liquid.
[0078] The liquid solvent may include a polar aprotic solvent, and may be selected from the group consisting of dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, propylene carbonate, ethylene carbonate, and esters such as ethyl acetate, ethyl propionate and methyl propionate, and mixtures thereof.
[0079] The liquid solvent may optionally be gelled by adding a polymer obtained, for example, from one or more monomers selected from the group consisting of ethylene oxide, propylene oxide, methyl methacrylate, methyl acrylate, acrylonitrile, methacrylonitrile, N-vinyl pyrrolidone and vinylidene fluoride, the polymer having a linear, comb, random, alternating or block structure and may be cross-linked or not.
[0080] The proportion of liquid solvent in the solvent may vary in the range of about 2 volume % (corresponding to the plasticizing solvent) to about 98 volume % (corresponding to the gelling solvent).
[0081] Preferably, the electrolyte comprises at least one salt selected from the group consisting of sodium hexafluorophosphate (NaPF6), sodium perchlorate (NaClO4), sodium bis(fluorosulfonyl)imide (NaFSI), sodium bis(trifluoromethanesulfonyl)imide (NaTFSI), sodium bis(pentafluoroethanesulfonyl)imide (NaBETI), sodium tetrafluoroborate (NaBF4) and mixtures thereof.
[0082] When the electrolyte is a liquid electrolyte, the liquid electrolyte will be injected into the battery with a separator. The separator can be a conventional polymer-based separator, such as Diaphragm or Borosilicate glass fiber separators, or cellulose based separators, such as Nonwoven nanofiber separator. Advantageously, the electrolyte is a solution comprising a sodium salt and one or more carbonates selected from the group consisting of ethylene carbonate, propylene carbonate, dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, vinylene carbonate and fluoroethylene carbonate.
[0083] The electrolyte may further include a group consisting of: vinylene carbonate (VC) (amount of 0.1 to 10 wt %, preferably 0.5 to 5.0 wt %), 1,3-propane sultone (PS) (amount of 0.1 to 5 wt %, preferably 0.5 to 3.0 wt %), succinonitrile (SN) (amount of 0.1 to 5 wt %, preferably 0.5 to 2.0 wt %), sodium difluoro(oxalato)borate (NaODFB) (amount of 0.05 to 10 wt %, preferably 0.2 to 1.0 wt %). In order to achieve high temperature performance and low self-discharge performance of Na-ion batteries, the additives can be used alone or in combination.
[0084] The electrolyte can be prepared by adding the salt to the solvent under stirring and then adding the additive to the obtained solution. The order of addition can be changed, for example, the additive is first added to the solvent and then the salt is added. The entire preparation process is carried out under an inert atmosphere (under argon or nitrogen).
[0085] application
[0086] The present invention also relates to the use of the material of formula (I) as defined above as positive electrode active material for Na-ion batteries.
[0087] The present invention also relates to a positive electrode comprising at least one material of formula (I). The positive electrode may further comprise a current collector.
[0088] Sodium-ion battery
[0089] The present invention also relates to a Na-ion battery comprising at least one positive electrode as defined above, at least one negative electrode and at least one electrolyte as defined above, and is prepared as described above.
[0090] The Na-ion battery implemented in the method of the present invention can be a half-cell using metallic sodium as the negative electrode, or a full cell using hard carbon as the negative electrode. Typically, the Na-ion battery is a button cell, a soft pack cell, a cylindrical cell or a square cell.
[0091] The Na-ion battery may further include at least one separator selected from glass fiber, a polyolefin separator including polypropylene (PP), polyethylene (PE) or a polypropylene / polyethylene / polypropylene film.
[0092] The Na-ion battery can be composed of a single electrochemical cell comprising two electrodes (i.e., a positive electrode and a negative electrode) separated by an electrolyte; or composed of multiple chemical cells assembled in series; or composed of multiple chemical cells assembled in parallel; or a combination of the two types of assembly.
[0093] The positive electrode, separator and negative electrode can be stacked layer by layer (one electrode and one separator) before being folded and wound into a battery core. The core is then placed in a battery case. Thereafter, the battery is dried at 85°C under vacuum for about 24 hours. The electrolyte is then injected into the battery before the battery is sealed to assemble a Na-ion battery.
[0094] Due to the fact that the third sodium ion can be reversibly removed from the material of formula (I), the reversible capacity and energy density of Na-ion batteries comprising the material are increased. BRIEF DESCRIPTION OF THE DRAWINGS
[0095] Figure 1 The voltage (V) at which the discharge potential is limited to 3 V for a sodium half-cell with an NVPF positive electrode is related to the variation in the amount of sodium in the material of formula (I).
[0096] Figure 2 Involved Figure 1 The derivative plot of the discharge curve in is used as a fingerprint to track the extent of in situ electrochemical modification induced in the material of formula (I).
[0097] Figure 3 Concerning the variation of voltage (V) with respect to the amount of sodium in the material of formula (I) for a sodium half-cell having a NVPF positive electrode according to the invention (cycling between 3-4.3 V).
[0098] Figure 4 For a sodium half-cell with a NVPF positive electrode according to the present invention, the capacity (in mAhg -1 The change in the voltage (in units) relative to the number of cycles (cycling between 3-4.3 V).
[0099] Figure 5 It relates to the change in the voltage (V) at which the discharge voltage is limited to 2V in a sodium ion full battery using a hard carbon negative electrode and an NVPF positive electrode according to the present invention relative to the amount of sodium in the material of formula (I).
[0100] Figure 6 For a sodium ion full battery with a hard carbon negative electrode and a NVPF positive electrode according to the present invention, the energy (in Wh.Kg -1The change in V (in units) relative to the number of cycles (cycling between 2-4.3 V).
[0101] Figure 7 Concerning the sodium half-cell with NVPF positive electrode according to the present invention, the discharge potential is limited to the change in voltage (V) of 1 V with respect to the amount of sodium in the material of formula (I).
[0102] Figure 8 Concerning the variation of voltage (V) with respect to the amount of sodium in the material of formula (I) for a sodium half-cell having a NVPF positive electrode according to the invention (cycling between 1-4.3 V).
[0103] Fig. 9 For a sodium half-cell with a NVPF positive electrode according to the present invention, the capacity (in mAhg -1 The change in V (in units) with respect to the number of cycles (cycling between 1-4.3 V).
[0104] Fig.10 It relates to the change of the voltage (V) when the discharge voltage is reduced to 0V relative to the amount of sodium in the material of formula (I) in a sodium ion full battery using a hard carbon negative electrode and an NVPF positive electrode according to the present invention.
[0105] Fig.11 It is related to the invention having mixed layered oxide Na x The discharge potential of the NVPF sodium half-cell with MO2 positive electrode is limited to 1.8V. The voltage (V) is related to the capacity (in mAh.g -1 as units). DETAILED DESCRIPTION
[0106] The present invention is explained in more detail in the following examples, but the present invention is not limited to these examples.
[0107] Example 1: Preparation of the material of formula (I)
[0108] Material (A) was electrochemically modified by charging it to a potential above 4.3 V and removing more than 2 sodium atoms from the structure.
[0109] Electrochemical sodium removal was performed in a half-cell with metallic sodium as the negative electrode or in a full cell with a Na-host material such as hard carbon, antimony, phosphorus, etc. as the negative electrode. In both cases, 1M (mol / L) NaPF6 dissolved in propylene carbonate was used as the electrolyte. Figure 1The charge curve shown in shows that the process of extracting the third sodium from the structure of material (A) is carried out in the third plateau at 4.75 V. The charging process is controlled by limiting the amount of sodium removed from the NVPF structure during the first charge to 2, 2.25, 2.5 and 2.75, etc. The material of formula (I) thus formed is hereinafter represented as 'NVPFΔx', where Δx is the amount of sodium removed from the structure of material (A) during the first charge to induce electrochemical modification.
[0110] For example, NVPF2.25 represents a material of formula (I) where x = 2.25.
[0111] In the subsequent discharge ( Figure 1 On the discharge curves in ( ), it is observed that the curve shape changes from a two-phase plateau (NVPF2.0) to an S shape (NVPF2.25, etc.), and the degree of modification increases with the increase in the amount of sodium extraction during the first charge. This change in the discharge curve shape indicates structural modification caused by the extraction of more than 2 sodium ions from material (A). Figure 2 The derivative of the discharge curve is used as a fingerprint to track the degree of structural modification. Figure 3 and 4 As shown, the modification thus produced is irreversible, and the battery cycles through an S-shaped curve in continuous cycles with considerable capacity retention. This change in the cycling curve from a flat (NVPF2.0) to an S-shaped (NVPF>2) is conducive to accurately measuring and controlling the battery potential at a given state of charge (SOC) and depth of discharge (DOD), thus helping to simplify the battery management system in practical applications.
[0112] Example 2: Improving the energy density of sodium ion batteries using materials of formula (I)
[0113] It is necessary to extract more than 2 sodium ions from material (A) to prepare the material of formula (I). The excess sodium (higher than 2) removed from material (A) is used to compensate for the sodium loss caused by the formation of the solid electrolyte interface layer in the negative hard carbon electrode in the sodium ion full cell. Figure 5 The cycling behavior of a full cell assembled with equal mass balance between the positive NVPF electrode and the negative hard carbon electrode is shown. Figure 6 As shown in Figure 2, an increase in reversible capacity can be observed by migrating from NVPF2 to NVPF2.35, resulting in an increase in the overall energy density of about 10%. The in-situ prepared material of formula (I) also provides a better battery cycle life ( Figure 6 ), because the cycling is carried out through the S-shaped solid solution, rather than keeping the battery in a high voltage (4.2V) plateau for a long time like NVPF2.0.
[0114] Example 3: Application of the material of formula (I) in over-discharge protection of sodium ion batteries
[0115] The excess sodium (greater than 2) removed from the NVPF to form the material of formula (I) can be reinserted into the material by discharging the cell to 1 V ( Figure 7 ). Therefore, if Figure 8 As shown, the in-situ electrochemically modified NVPF structure can have a higher sodium reversible cycle (for NVPF2.75, Δx = 2.82) compared to material (A) (for NVPF2.0, Δx = 2.21). This will increase the specific capacity, and all materials show comparable capacity retention ( Fig. 9 ). In addition, inserting sodium into the NVPF structure at low potential (<1.5V) can also be used as a protection for the battery against over-discharge. Fig.10 As shown, sodium ion batteries having materials of formula (I) can be discharged to 0 V without causing any sodium oxidation of the solid electrolyte interphase and the associated detrimental problems.
[0116] Example 4: Use of the material of formula (I) for obtaining a hybrid electrode with high gravimetric and volumetric energy density
[0117] Na3V2(PO4)2F3 and layered Na x MO2 (x<1, M=transition metal ion) (material (B)) was mixed and used as the positive electrode of sodium ion battery. 3 ) materials, layered sodium transition metal oxides offer higher densities (typically 4-5 g / cm 3 ). Therefore, in terms of volumetric energy density, sodium layered oxides offer better advantages. However, P2, P3 and some O3 layered oxides (such as Na x Cu y Fe z Mn 1-y-z O2) is non-stoichiometric and requires an additional sodium source in the battery for Na x MO2 is electrochemically converted to Na1MO2 to increase its gravimetric energy density. This is achieved by mixing NVPF with sodium layered oxides and activating the NVPF for more than 2 Na extraction. The sodium removed from the NVPF (more than 2) is used for Na x Electrochemical conversion of MO2 to Na1MO2 ( Fig.11 ). Here we use P2 type Na 2 / 3 Mg 0.3 Mn 0.7 O2 is used to explain the proof of concept. Similar principles can be extended to other P2, P3 Na x MO2 phase and O3 phase with Na / M ratio <1 (e.g. Nax With y Fe z min 1-y- z O2).
Claims
1. A positive electrode material, wherein: The general formula of the positive electrode material is shown in Formula I below: Na 3-x □ x V (2-y) M y (PO4)2F (3-z) O z / 2 I in: 2<x≤3; 0≤y≤1; 0≤z≤1; □ represents a vacancy; and M represents a transition or non-transition metal ion selected from the group consisting of magnesium, zinc, iron, aluminum, nickel, cobalt, chromium, titanium, manganese and mixtures thereof, Wherein, the positive electrode material shown in Formula I has a structure of a tetragonal space group I4 / mmm, Wherein, Na in Formula I 3-x □ x The positive electrode material represented by Formula I can reversibly absorb and remove more than two sodium ions.
2. The positive electrode material according to claim 1, wherein The M is aluminum.
3. The positive electrode material according to claim 1 or 2, wherein y=0 and / or z=0.
4. The positive electrode material according to claim 1 or 2, wherein x is 2.25, 2.35, 2.5, or 2.
75.
5. A method for preparing a positive electrode material according to any one of claims 1 to 4, comprising the following steps: i) preparing a Na-ion battery comprising at least one positive electrode, at least one negative electrode and at least one electrolyte, wherein the positive electrode comprises a Na-based material A selected from the group consisting of: Na3V2(PO4)2F3, Na3V (2-y) M y (PO4)2F3、Na3V (2-y) M y (PO4)2F (3-z) O z / 2 and mixtures thereof; y, z and M are as defined in any one of claims 1 to 4; ii) making the Na ion battery obtained at the end of step i) relative to Na + / Na 0 The battery is charged at a constant current and constant voltage at a potential of 4.3 V to 4.8 V, and the battery is kept at such a potential until more than two Na ions are reversibly extracted from material A, wherein the amount of Na ions is determined by coulometric method; and iii) obtaining a positive electrode material as shown in formula I.
6. The method according to claim 5, wherein: In the step ii), the Na ion battery obtained at the end of step i) is + / Na 0 The battery was charged at a potential of 4.8 V with constant current and constant voltage.
7. The method according to claim 5, wherein: The positive electrode further comprises a Na-based oxide material B of formula Na x’ M’O2, where 0 < x’ ≤ 1, and M’ represents a metal ion selected from the group consisting of nickel, zinc, cobalt, manganese, iron, chromium, titanium, copper, vanadium, aluminum, magnesium, and mixtures thereof. The amount of material A is 0.1 wt% to 100 wt% relative to the total amount of the electrode material, and the amount of material B is 0 wt% to 99.9 wt%.
8. The method according to any one of claims 5 to 7, wherein: The negative electrode includes a material C selected from the group consisting of hard carbon, antimony, tin, sodium, phosphorus, and a mixture thereof.
9. The method according to any one of claims 5 to 7, wherein: The positive electrode also includes a current collector and is prepared according to the following steps: a) mixing material A with a binder and an electronic conductive agent to obtain a mixture; b) dispersing the mixture obtained in step a) in a solvent to form a slurry; c) casting the slurry obtained at the end of step b) on a current collector to obtain a positive electrode; d) drying the positive electrode obtained at the end of step c) at a temperature of 60° C. to 300° C.; e) pressing the dried positive electrode obtained at the end of step d) using a roller press.
10. The method according to claim 9, wherein: In said step d), the positive electrode obtained at the end of step c) is dried at a temperature of 120°C.
11. The method according to any one of claims 5 to 7, wherein: The electrolyte includes a solvent selected from the group consisting of dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, propylene carbonate, ethylene carbonate, ethyl acetate, ethyl propionate, methyl propionate, and a mixture thereof.
12. The method according to any one of claims 5 to 7, wherein: The electrolyte includes a salt selected from the group consisting of sodium hexafluorophosphate, sodium perchlorate, sodium bis(fluorosulfonyl)imide, sodium bis(trifluoromethanesulfonyl)imide, sodium bis(pentafluoroethanesulfonyl)imide, sodium tetrafluoroborate, and mixtures thereof.
13. The method according to any one of claims 5 to 7, wherein: The Na-ion battery is a half-cell using metallic sodium as a negative electrode, or a full-cell using hard carbon as a negative electrode.
14. The method according to any one of claims 5 to 7, wherein: The Na-ion battery is a button battery, a soft pack battery, a cylindrical battery or a square battery.
15. Use of the cathode material according to any one of claims 1 to 4 as a cathode active material for a Na-ion battery.
16. A positive electrode for a Na-ion battery, comprising at least one positive electrode material according to any one of claims 1 to 4.
17. A Na-ion battery comprising at least one positive electrode as claimed in claim 16, at least one negative electrode and at least one electrolyte.